2023
DOI: 10.1186/s12913-023-09029-y
|View full text |Cite
|
Sign up to set email alerts
|

Operational flexibility impact on hospital performance through the roles of employee engagement and management capability

Abstract: Background Very limited empirical research has been done on operational flexibility management in the healthcare industry, especially in hospital settings. This study aimed to propose a model of the effects of operational flexibility on hospital performance through management capability and employee engagement as mediating variables. Methods The proposed model is validated through an empirical study among 480 clinical and administrative staff from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…After the action plan, the rehabilitation staff were dissatisfied with the increased flexibility in ward regulations and subsequent disorderliness in the ward. Contrarily, a study showed that flexibility in service provision had significant positive effects on functioning and improved family participation in care ( 77 ). This contradiction may be due to the chronic course of child disability and the long hospital stay of children and their families in the rehabilitation ward.…”
Section: Discussionmentioning
confidence: 99%
“…After the action plan, the rehabilitation staff were dissatisfied with the increased flexibility in ward regulations and subsequent disorderliness in the ward. Contrarily, a study showed that flexibility in service provision had significant positive effects on functioning and improved family participation in care ( 77 ). This contradiction may be due to the chronic course of child disability and the long hospital stay of children and their families in the rehabilitation ward.…”
Section: Discussionmentioning
confidence: 99%
“…Fleksibilitas kerja memiliki pengaruh yang besar terhadap kualitas kehidupan kerja mereka sebagai karyawan, yang mana dapat meningkatkan job engagement di perusahaan (Prabowo et al, 2023). Job engagement, diketahui secara empiris, dipengaruhi oleh fleksibilitas kerja; hal ini dibuktikan oleh hasil-hasil studi yang pernah dilakukan pada 480 orang karyawan klinis dan administrasi di Yordania (Alolayyan & Alyahya, 2023), 208 orang karyawan swasta dan publik di Jakarta (Witriaryani et al, 2022), serta 45 orang karyawan konstruksi di Jakarta (Johanes & Prasadjaningsih, 2016). Dengan demikian, berdasarkan paparan kajian empiris tersebut, dapat ditarik suatu hipotesis riset berikut ini.…”
Section: Tinjauan Pustakaunclassified
“…In line with this vision, Yousuf et al ( 2019) also highlight the same for operational flexibility. Moreover, Alolayyan and Alyahya (2023) also point out that operational flexibility and management capability enhance organizational responsiveness and influence performance. We make the following hypotheses based on these arguments:…”
Section: Strategic Flexibility Operational Flexibility and Performancementioning
confidence: 99%